Speech development delay in a child with foetal alcohol syndrome - Wilczyński, Jacek; Jabłońska, Jolanta (Medical Studies/Studia Medyczne, 2016)
A female foetus in her mother’s womb was exposed to high concentrations of alcohol at each stage of pregnancy on a long-term basis, which resulted in a permanent disability. In addition to a number of deficiencies in the overall functioning of the body of the child, there are serious problems pertaining to verbal communication. This thesis aims to describe foetal alcohol syndrome (FAS) disease and present the basic problems with communication functions in a child, caused by damage of brain structures responsible for speech development. The thesis includes a speech diagnosis and therapy program adapted to the presented case. In the Discussion Section we have presented characteristics of communication disorders in case of children with FAS and the description of developmental malformations, neurobehavioral disorders, and environmental factors affecting the development of the child’s speech.